CD147 promotes progression of head and neck squamous cell carcinoma via NF‐kappa B signaling. Issue 2 (12th November 2018) - Yu, Binbin; Zhang, Yan; Wu, Kailiu; Wang, Lizhen; Jiang, Yingying; Chen, Wantao; Yan, Ming
Abstract: CD147/basigin (BSG) is highly upregulated in many types of cancer, our previous study has found that CD147/BSG is highly expressed in head and neck squamous cell carcinoma (HNSCC) stem cells, but its role in HNSCC and the underlying mechanism is still unknown. In this study, we investigated the role of CD147 in the progression of HNSCC. Real‐time PCR, western blot and immunohistochemistry were used to detect the expression of CD147 in total 189 HNSCC tissues in compared with normal tissues. In addition, we used proliferation, colony formation, cell cycle and apoptosis, migration and invasion as well as wound‐healing assay to determine the biological roles of CD147 in HNSCC. Then, a xenograft model was performed to evaluate tumor‐promoting and metastasis‐promoting role of CD147 in HNSCC. The results showed that upregulated CD147 expression was associated with aggressive clinicopathologic features in HNSCC. In addition, CD147 promoted proliferation, migration and reduced the apoptosis phenotype of HNSCC cells in vitro as well as tumor initiation and progression in vivo. Furthermore, we demonstrated that CD147 promoted HNSCC progression through nuclear factor kappa B signaling. Therefore, we concluded that CD147 promoted tumor progression in HNSCC and might be a potential prognostic and treatment biomarker for HNSCC.